2002
DOI: 10.1074/jbc.m109615200
|View full text |Cite
|
Sign up to set email alerts
|

Residence of Adenylyl Cyclase Type 8 in Caveolae Is Necessary but Not Sufficient for Regulation by Capacitative Ca2+Entry

Abstract: (2000) J. Biol. Chem. 275, 26530 -26537). In the present study, we established that depletion of cellular cholesterol ablated the regulation by CCE of a Ca 2؉ -stimulable adenylyl cyclase, AC8, heterologously expressed in HEK293 cells. We considered the possibility that a calmodulin-binding domain in the N terminus of AC8, which is not required for in vitro regulation by Ca 2؉ , might play a targeting role. Deletion and mutation of the N terminus did attenuate the enzyme's sensitivity to CCE without altering i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
107
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(115 citation statements)
references
References 42 publications
6
107
2
Order By: Relevance
“…8, Western blotting of HEK 293 cell membrane fractions using an NHE1-specific monoclonal antibody showed high expression of the exchanger in fractions 4 and 5, alongside caveolin (the marker of lipid rafts) and transiently expressed AC8. The latter is consistent with previous studies in our laboratory showing that the AC8 protein is enriched in these caveolin-containing fractions (24). A small amount of NHE1 was found in fractions 7-9, which corresponded to the bulk plasma membrane regions, as identified by the marker ␤-adaptin (37).…”
Section: Nhe1 Activity Protects Ac8 From Local Acid Shifts In Hek 293supporting
confidence: 81%
See 3 more Smart Citations
“…8, Western blotting of HEK 293 cell membrane fractions using an NHE1-specific monoclonal antibody showed high expression of the exchanger in fractions 4 and 5, alongside caveolin (the marker of lipid rafts) and transiently expressed AC8. The latter is consistent with previous studies in our laboratory showing that the AC8 protein is enriched in these caveolin-containing fractions (24). A small amount of NHE1 was found in fractions 7-9, which corresponded to the bulk plasma membrane regions, as identified by the marker ␤-adaptin (37).…”
Section: Nhe1 Activity Protects Ac8 From Local Acid Shifts In Hek 293supporting
confidence: 81%
“…Cariporide was a gift from Dr. Juergen Puenter at Avetis Pharma (Frankfurt, Germany). Polyclonal AC8 antibody was a gift from Dr. J. J. Cali, as previously described (24). Polyclonal caveolin antibody was obtained from BD Transduction Laboratories (Erembodegem, Belgium), and polyclonal ␤-adaptin antibody was from Santa Cruz Biotechnology, Inc. (Santa Cruz, CA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that expression of specific isoforms, subcellular localization, and differential regulation of ACs greatly contribute to the diverse and tissue-specific regulation of cAMP (33)(34)(35)(36)(37). Here we report a novel regulatory pathway for control of cAMP synthesis in three hematopoietic cell lines.…”
Section: Discussionmentioning
confidence: 99%